Cognition in the cockpit: assessing instructional modalities in pilot training simulations - Rochon, Laurie-Jade; Karran, Alexander John; Rolon-Merette, Thadde; Courtemanche, François; Coursaris, Constantinos; Senecal, Sylvain; Léger, Pierre-Majorique (Frontiers in Psychology, 2025)
IntroductionFlight Simulators (FS) play a critical role in pilot training, yet the increasing use of automated modules in FS raises questions about how instructional delivery methods influence learning. This study investigates how different FS instruction modalities affect student pilots’ cognitive states and performance.MethodsA between-subjects experiment was conducted with 30 flight-school students using Microsoft Flight Simulator 2020 under Visual Flight Rules (VFR). Participants were randomly assigned to one of three instruction modalities: audio-only, text-only, or combined audio-text. Each participant completed two tasks: (1) an instructional flight with guided instructions and (2) a solo evaluation flight without guidance. Measures included visual transition entropy (to assess visual scanning), emotional valence, cognitive load, motivation, and flight performance metrics.ResultsDuring the evaluation flight, the text-only and combined audio-text groups showed significantly lower visual transition entropy, indicating more organized visual scanning. The text-only group also exhibited higher emotional valence, reflecting greater motivation and engagement. No significant differences were found in overall flight performance or cognitive load, although trends suggested higher perceived immersion and motivation in the text-only condition.DiscussionTextual instructional delivery appears to support more efficient visual scanning and greater engagement, aligning with the Cognitive Theory of Multimedia Learning while highlighting its boundary conditions in aviation contexts. Although performance metrics were unaffected in this short session, textual information may be advantageous for specific flight segments and scenarios lacking live instruction. Further research should examine longer or repeated training sessions.